Frequency of Detection of Escherichia coli, Salmonella spp., and Campylobacter spp. in the Faeces of Wild Rats (Rattus spp.) in Trinidad and Tobago - Comfort Nkogwe; Juliah Raletobana; Alva Stewart-Johnson; Sharianne Suepaul; Abiodun Adesiyun (Veterinary Medicine International)
The study was conducted to determine the frequency of isolation of Salmonella, Campylobacter and E. coli O157 in the faecal samples of rats trapped across the regional corporations in Trinidad and to assess their resistance to antimicrobial agents. A total of 204 rats were trapped for the detection of selected bacteria. Standard methods were used to isolate Salmonella, Campylobacter and E. coli O157. Characterization of E. coli was done on sorbitol MacConkey agar to determine non-sorbitol fermentation, blood agar to determine haemolytic and mucoid colonies and by using E. coli O157 antiserum to determine O157 strain. The disc diffusion method was used to determine resistance to nine antimicrobial agents. Of the 204 rats, 4 (2.0%), 7 (3.4%) and 171 (83.8%) were positive for Salmonella spp., Campylobacter spp. and E. coli, respectively. Of the 171 isolates of E. coli tested 0 (0.0%), 25 (14.6%) and 19 (11.1%) were haemolytic, mucoid and non-sorbitol fermenters, respectively. All isolates were negative for the O157 strain. The frequency of resistance to the 9 antimicrobial agents tested was 75% (3 of 4) for Salmonella, 85.7% (6 of 7) of Campylobacter spp. and 36.3% (62 of 171) for E. coli (𝑃<.05; χ2).